Manajemen Dakwah Masjid Trans Studio Bandung dalam Mengakomodasi Jamaah Difabel - Hasya Aulia Adilah; Ida Afidah; Chairiawaty (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. As the center of Islamic da’wah, mosques must have adequate services and facilities for disabled worshipers. Every Muslim, regardless of their physical condition, has the right to benefit from da’wah activities. This research is entitled “Da’wah Management of Trans Studio Bandung Mosque in Accommodating Disabled Worshipers”. This study aims to determine the da’wah program followed by disabled worshipers, da’wah management in accommodating disabled worshipers, and the obstacles faced in carrying out da’wah management for disabled worshipers at the Trans Studio Bandung (TSB) Mosque. This type of research is qualitative, with a descriptive-analytical method, and uses George R. Terry’s (1958) management function theory. The results showed that the management of da’wah of the TSB Mosque in accommodating disabled worshipers in terms of da’wah programs and the fulfillment of disabled facilities consisted of a process of planning, organizing, actuating, and controlling. However, the da’wah management has not been implemented optimally, especially in the fulfillment of disability-friendly facilities. The main obstacles faced are limited physical facilities, a long approval process, and service difficulties. Abstrak. Sebagai pusat dakwah Islam, masjid harus memiliki layanan dan fasilitas yang memadai bagi jamaah difabel. Setiap Muslim, tanpa memandang kondisi fisiknya, memiliki hak untuk mendapatkan manfaat dari kegiatan dakwah. Penelitian ini berjudul “Manajemen Dakwah Masjid Trans Studio Bandung dalam Mengakomodasi Jamaah Difabel”. Penelitian ini bertujuan untuk mengetahui program dakwah yang diikuti jamaah difabel, manajemen dakwah dalam mengakomodasi jamaah difabel, serta kendala yang dihadapi dalam melaksanakan manajemen dakwah untuk jamaah difabel di Masjid Trans Studio Bandung (TSB). Jenis penelitian ini adalah kualitatif, dengan metode deskriptif-analisis, serta menggunakan teori fungsi manajemen George R. Terry (1958). Hasil penelitian menunjukkan bahwa manajemen dakwah Masjid TSB dalam mengakomodasi jamaah difabel dari segi program dakwah dan pemenuhan fasilitas difabel terdiri dari proses perencanaan, pengorganisasian, pelaksanaan, pengawasan. Akan tetapi manajemen dakwah tersebut belum dilaksanakan secara optimal terutama dalam pemenuhan fasilitas ramah difabel. Kendala utama yang dihadapi adalah keterbatasan fasilitas fisik, proses persetujuan yang panjang, dan kesulitan pelayanan.